Validity and Practicality of Colloid E-Learning Content Based on Individual Rotation Guided Inquiry for Senior High School - Viola Dwicha Asda; Eka Frima Asda; Fikri Aulia; Ahmad Asdi; Randy Jamal (INTERNATIONAL JOURNAL OF HIGH INFORMATION, COMPUTERIZATION, ENGINEERING AND APPLIED SCIENCE (JHICE), 2022)
Blended learning is an effective learning and efficient model that can be used during an pandemic Covid-19. One of the LMS available for online learning is E-Learning. This research produced e-learning based on individual rotation guided inquiry of colloid material in the learning process. To obtain an effective product, this research is carried out starting from identification, design, development and dissemination. The research carried out with the model with research and development (R&D) methods using a 4D development model. The E-learning products from this study were validated by four Chemisty teachers and the analysis of validity and praticality tests was carried out by 3 teachers and 10 students then analyzed using the kappa cohen formula. The kappa values obtained from the validity of the construct and the validity of the content are 0.88 and 0.89 with very high categories. The practicality results of students and teachers were 84.38 and 87.29 with high categories respectively. Based on the results of data analysis, it can be concluded that the E-Learning has valid and practical for use in the learning process.